Computational Support for Theoretical Chemistry: Report of a Conference Held at the National Institutes of Health, Bethesda, Maryland, May 8-9, 1970 (The National Academies Press, 1971)
Keywords: Math, Chemistry, and Physics

Substitute Catalysts for Platinum in Automobile Emission Control Devices and Petroleum Refining (The National Academies Press, 1973)
Keywords: Math, Chemistry, and Physics

Interdisciplinary Research: Promoting Collaboration Between the Life Sciences and Medicine and the Physical Sciences and Engineering (The National Academies Press, 1990)
Keywords: Math, Chemistry, and Physics

A Research Agenda for Transforming Separation Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Separation science plays a critical role in maintaining our standard of living and quality of life. Many industrial processes and general necessities such as chemicals, medicines, clean water, safe food, and energy sources rely on chemical separations. However, the process of chemical separations is often overlooked during product development and this has led to inefficiency, unnecessary waste, and lack of consensus among chemists and engineers. A reevaluation of system design, establishment of standards, and an increased focus on the advancement of separation science are imperative in supporting increased efficiency, continued U.S. manufacturing competitiveness, and public welfare.
Keywords: Math, Chemistry, and Physics

High Magnetic Field Science and Its Application in the United States: Current Status and Future Directions - National Research Council (The National Academies Press, 2013)
The Committee to Assess the Current Status and Future Direction of High Magnetic Field Science in the United States was convened by the National Research Council in response to a request by the National Science Foundation. This report answers three questions: (1) What is the current state of high-field magnet science, engineering, and technology in the United States, and are there any conspicuous needs to be addressed? (2) What are the current science drivers and which scientific opportunities and challenges can be anticipated over the next ten years? (3) What are the principal existing and planned high magnetic field facilities outside of the United States, what roles have U.S. high field magnet development efforts played in developing those facilities, and what potentials exist for further international collaboration in this area? A magnetic field is produced by an electrical current in a metal coil. This current exerts an expansive force on the coil, and a magnetic field is "high" if it challenges the strength and current-carrying capacity of the materials that create the field. Although lower magnetic fields can be achieved using commercially available magnets, research in the highest achievable fields has been, and will continue to be, most often performed in large research centers that possess the materials and systems know-how for forefront research. Only a few high field centers exist around the world; in the United States, the principal center is the National High Magnetic Field Laboratory (NHMFL). High Magnetic Field Science and Its Application in the United States considers continued support for a centralized high-field facility such as NHFML to be the highest priority. This report contains a recommendation for the funding and siting of several new high field nuclear magnetic resonance magnets at user facilities in different regions of the United States. Continued advancement in high-magnetic field science requires substantial investments in magnets with enhanced capabilities. High Magnetic Field Science and Its Application in the United States contains recommendations for the further development of all-superconducting, hybrid, and higher field pulsed magnets that meet ambitious but achievable goals.
Keywords: Math, Chemistry, and Physics

The Future of U.S. Chemistry Research: Benchmarks and Challenges - National Research Council (The National Academies Press, 2007)
Chemistry plays a key role in conquering diseases, solving energy problems, addressing environmental problems, providing the discoveries that lead to new industries, and developing new materials and technologies for national defense and homeland security. However, the field is currently facing a crucial time of change and is struggling to position itself to meet the needs of the future as it expands beyond its traditional core toward areas related to biology, materials science, and nanotechnology.
Keywords: Math, Chemistry, and Physics

Assessing the Value of Research in the Chemical Sciences - National Research Council (The National Academies Press, 1998)
This book captures the messages from a workshop that brought together research managers from government, industry, and academia to review and discuss the mechanisms that have been proposed or used to assess the value of chemical research. The workshop focused on the assessment procedures that have been or will be established within the various organizations that carry out or fund research activities, with particular attention to the Government Performance and Results Act (GPRA). The book presents approaches and ideas from leaders in each area that were intended to identify new and useful ways of assessing the value and potential impact of research activities.
Keywords: Math, Chemistry, and Physics

Advancing Chemistry and Quantum Information Science: An Assessment of Research Opportunities at the Interface of Chemistry and Quantum Information Science in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The field of quantum information science (QIS) has witnessed a dramatic rise in scientific research activities in the 21st century as excitement has grown about its potential to revolutionize communications and computing, strengthen encryption, and enhance quantum sensing, among other applications. While, historically, QIS research has been dominated by the field of physics and computer engineering, this report explores how chemistry - in particular the use of molecular qubits - could advance QIS. In turn, researchers are also examining how QIS could be used to solve problems in chemistry, for example, to facilitate new drug and material designs, health and environmental monitoring tools, and more sustainable energy production. Recognizing that QIS could be a disruptive technology with the potential to create groundbreaking products and new industries, Advancing Chemistry and Quantum Information Science calls for U.S. leadership to build a robust enterprise to facilitate and support research at the intersection of chemistry and QIS. This report identifies three key research areas: design and synthesis of molecular qubit systems, measurement and control of molecular quantum systems, and experimental and computational approaches for scaling qubit design and function. Advancing Chemistry and Quantum Information Science recommends that the Department of Energy, National Science Foundation, and other funding agencies should support multidisciplinary and collaborative research in QIS, the development of new instrumentation, and facilities, centralized and open-access databases, and efforts to create a more diverse and inclusive chemical workforce.
Keywords: Math, Chemistry, and Physics

Possible Health Effects of Exposure to Residential Electric and Magnetic Fields - National Research Council (The National Academies Press, 1997)
Can the electric and magnetic fields (EMF) to which people are routinely exposed cause health effects? This volume assesses the data and draws conclusions about the consequences of human exposure to EMF. The committee examines what is known about three kinds of health effects associated with EMF: cancer, primarily childhood leukemia; reproduction and development; and neurobiological effects. This book provides a detailed discussion of hazard identification, dose-response assessment, exposure assessment, and risk characterization for each. Possible Health Effects of Exposure to Residential Electric and Magnetic Fields also discusses the tools available to measure exposure, common types of exposures, and what is known about the effects of exposure. The committee looks at correlations between EMF exposure and carcinogenesis, mutagenesis, neurobehavioral effects, reproductive and developmental effects, effects on melatonin and other neurochemicals, and effects on bone healing and stimulated cell growth.
Keywords: Environment and Environmental Studies; Math, Chemistry, and Physics

Regional Dialogues on the Changing Environment for the Physical and Mathematical Sciences: Report of Two Conferences (The National Academies Press, 1995)

Radiochemistry of Mercury - National Research Council (The National Academies Press, 1970)

Technological Challenges in Antibiotic Discovery and Development: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Technological Challenges in Antibiotic Discovery and Development is the summary of a workshop convened by the Chemical Sciences Roundtable in September 2013 to explore the current state of antibiotic discovery and examine the technology available to facilitate development. Through formal presentations and panel discussions, participants from academia, industry, federal research agencies discussed the technical challenges present and the incentives and disincentives industry faces in antibiotic development, and identified novel approaches to antibiotic discovery. Antibiotic resistance is a serious and growing problem in modern medicine and it is emerging as a pre-eminent public health threat. Each year in the United States alone, at least two million acquire serious infections with bacteria that are resistant to one or more antibiotics, and at least 23,000 people die annually as a direct result of these antibiotic-resistant infections. In addition to the toll on human life, antibiotic-resistant infections add considerable and avoidable costs to the already overburdened U.S. health care system. This report explores the challenges in overcoming antibiotic resistance, screening for new antibiotics, and delivering them to the sites of infection in the body. The report also discusses a path forward to develop the next generation of potent antimicrobial compounds capable of once again tilting the battle against microbial pathogens in favor of humans. Technological Challenges in Antibiotic Discovery and Development gives a broad view of the landscape of antibiotic development and the technological challenges and barriers to be overcome.
Keywords: Math, Chemistry, and Physics

The Chemistry of Microbiomes: Proceedings of a Seminar Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The 21st century has witnessed a complete revolution in the understanding and description of bacteria in eco- systems and microbial assemblages, and how they are regulated by complex interactions among microbes, hosts, and environments. The human organism is no longer considered a monolithic assembly of tissues, but is instead a true ecosystem composed of human cells, bacteria, fungi, algae, and viruses. As such, humans are not unlike other complex ecosystems containing microbial assemblages observed in the marine and earth environments. They all share a basic functional principle: Chemical communication is the universal language that allows such groups to properly function together. These chemical networks regulate interactions like metabolic exchange, antibiosis and symbiosis, and communication.
Keywords: Math, Chemistry, and Physics

Experiments in International Benchmarking of US Research Fields - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2000)
How can the federal government gauge the overall health of scientific research—as a whole and in its parts—and determine whether national funding adequately supports national research objectives? It is feasible to monitor US performance with field-by-field peer assessments. This might be done through the establishment of independent panels consisting of researchers who work in a field, individuals who work in closely related fields, and research "users" who follow the field closely. Some of these individuals should be outstanding foreign scientists in the field being examined. This technique of comparative international assessments is also known as international benchmarking. Experiments in International Benchmarking of U.S. Research Fields evaluates the feasibility and utility of the benchmarking technique. In order to do this, the report internationally benchmarks three fields: mathematics, immunology, and materials science and engineering, then summarizes the results of these experiments.
Keywords: Math, Chemistry, and Physics

Water Chemicals Codex - Institute of Medicine; National Research Council (The National Academies Press, 1982)
Keywords: Math, Chemistry, and Physics

Issues in Risk Assessment - National Research Council (The National Academies Press, 1993)
The scientific basis, inference assumptions, regulatory uses, and research needs in risk assessment are considered in this two-part volume. The first part, Use of Maximum Tolerated Dose in Animal Bioassays for Carcinogenicity, focuses on whether the maximum tolerated dose should continue to be used in carcinogenesis bioassays. The committee considers several options for modifying current bioassay procedures. The second part, Two-Stage Models of Carcinogenesis, stems from efforts to identify improved means of cancer risk assessment that have resulted in the development of a mathematical dose-response model based on a paradigm for the biologic phenomena thought to be associated with carcinogenesis.
Keywords: Math, Chemistry, and Physics

Atomic, Molecular, and Optical Science: An Investment in the Future - National Research Council (The National Academies Press, 1994)
This book responds to the call for a clear description of the role of basic science in meeting societal needs. It gives examples of societal benefits of atomic, molecular, and optical (AMO) science in a number of key areas, including industrial technology, information technology, energy, global change, defense, health and medical technology, space technology, and transportation. This volume highlights the role of lasers in trapping, cooling, and manipulating individual atoms and molecules to make possible ultraprecise atomic clocks, structural engineering at the atomic level (nanotechnology), and new approaches to the study of deoxyribonucleic acid (DNA). AMO science is shown to be a field that is both an intellectually important basic science and a powerful enabling science that supports many other areas of science and technology.
Keywords: Math, Chemistry, and Physics

Opportunities in Chemistry: Today and Tomorrow - Pimentel, George C.; Coonrod, Janice A. (The National Academies Press, 1987)
Experts agree that the nation would benefit if more young people "turned on" to the sciences. This book is designed as a tool to do just that. It is based on Opportunities in Chemistry, a National Research Council publication that incorporated the contributions of 350 researchers working at the frontiers of the field. Chemistry educators Janice A. Coonrod and the late George C. Pimentel revised the material to capture the interest of today's student. A broad and highly readable survey, the volume explores:
Keywords: Math, Chemistry, and Physics

Why Indoor Chemistry Matters - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
People spend the vast majority of their time inside their homes and other indoor environments where they are exposed to a wide range of chemicals from building materials, furnishings, occupants, cooking, consumer products, and other sources. Despite research to date, very little is known about how exposures to indoor chemicals across complex chemical phases and pathways affect human health. The COVID-19 pandemic has only increased public awareness of indoor environments and shed light on the many outstanding questions about how best to manage chemicals indoors. This report identifies gaps in current research and understanding of indoor chemistry and new approaches that can be applied to measure, manage, and limit chemical exposures. Why Indoor Chemistry Matters calls for further research about the chemical transformations that can occur indoors, pathways and timing of indoor chemical exposure, and the cumulative and long-term impacts of exposure on human health. Research priorities should consider factors that contribute to measurable environmental health disparities that affect vulnerable populations, such as the age, location, and condition of buildings that can alter exposures to indoor chemicals.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies

Innovations in Pharmaceutical Manufacturing on the Horizon: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Emerging technologies have the potential to modernize pharmaceutical manufacturing and advance the quality of drug products. A 2021 report from the National Academies of Sciences, Engineering, and Medicine (the National Academies) identified these innovative technologies, including manufacturing processes, control and testing strategies, and product technologies. The report, Innovations in Pharmaceutical Manufacturing on the Horizon: Technical Challenges, Regulatory Issues, and Recommendations, also discussed technical and regulatory challenges to implementing these technologies and provided suggestions for overcoming some of those issues. A virtual dissemination workshop titled Innovations in Pharmaceutical Manufacturing on the Horizon was hosted by the National Academies on October 28-29, 2021, and provided a venue for discussing the 2021 National Academies report's recommendations and a platform for members of the report committee to reflect on the study. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that took place during the dissemination workshop.
Keywords: Health and Medicine; Math, Chemistry, and Physics